Exclusive breastfeeding among HIV exposed infants from birth to 14 weeks of life in Lira, Northern Uganda: a prospective cohort study - Napyo, Agnes; Tumwine, James K.; Mukunya, David; Waako, Paul; Tylleskär, Thorkild; Ndeezi, Grace (Global Health Action, 2020)
Breastfeeding is important for growth, development and survival of HIV exposed infants. Exclusive breastfeeding reduces the risk of morbidity, mortality and increases HIV free survival of infants. Evidence on risk factors for inappropriate breastfeeding in Northern Uganda is limited. Objective: This study determined the risk factors for non-exclusivity of breastfeeding in the first 14 weeks of life.
Keywords: Breastfeeding; innfants; Infant feeding; Mixed feeding; Women living with HIV